MENGANALISIS STRUKTUR FISIK PUISI "DALAM DOAKU" KARYA DARI SAPARDI DJOKO DAMONO - nurani, titih; sudrajat, Rochmat Tri; Suhara, Alfa Mitri (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
The background of this research is based on an interest in studying the physical structure in poetry. Because it can be seen from the very simple choice of words. Even though it is taken from everyday language, it can produce a distinct beauty. Able to make readers understand the meaning conveyed, so that they are carried away with the poetry as in the poem "in my prayer"  by Sapardi Djoko Damono. The purpose of this study 1) to analyze the physical structure "in my prayer" by Sapardi Djoko Damono, 2) to describe the poems in my prayer by Sapardi Djoko Damono in sound and language. In this study using a qualitative descriptive method is a method used to find knowledge of research subjects at a certain time. This study also uses a structural approach. The subject is the poem in prayer by Sapardi Djoko Damono. The results of this study can be seen  in terms of sound divided into several parts, namely rhyme, kakafoni and ephony, onomatopoeia, anaphora and epiphora, asonation, and alliteration. Where as in language there are vocabulary, choice of words or diction, images or pengimajian (sight, hearing, smell, taste, touch, and movement). Language with language (comparison, personification, metaphor, allegory, parable, metonomia, and synekdoke), rhetorical language, concrete language, grammar, and typography of language. So, the sound and language will be analyzed one by one. As for the topic of this research, it is able to inspire everyone to be able to make literary works better by paying attention to the structure contained in poetry.Keywords: Rhymes, Sounds, Sapardi Djoko Damono